Evaluation of a modified German version of the Q16 questionnaire for neurotoxic symptoms in workers exposed to solvents - Ihrig, Andreas; Triebig, Gerhard; Dietz, Michael Christof (Occupational and environmental medicine, 2001)
OBJECTIVES: To assess sensitivity and specificity of a questionnaire designed to detect neurotoxic symptoms in workers exposed to solvents and in patients with a psycho-organic syndrome. METHODS: The Swedish Q16 is a self administered questionnaire for neurotoxic symptoms. The modified German version consists of 18 questions. The results were analysed from 1166 questionnaires which were completed by adults belonging to the following groups; 483 workers with occupational exposure to solvents and 193 non-exposed controls, 25 patients with a psycho-organic syndrome, 25 sex and age matched patients with a lung disease, and a sample of 440 people from the general population. RESULTS: The German Q18 was easy to handle and quick to perform. Workers exposed to solvents reported significantly more complaints than controls (2.9 v 2.5). All patients with a psycho-organic syndrome had five or more complaints. This was true for only 32% of patients with lung disease. These comparisons showed that chronic exposure to solvents was associated with subjective complaints related particularly to cognitive functions. In the sample of the general population, age, education level, smoking habits, and time of performance showed no significant influence on the Q18 result. Women had significantly more complaints than men (3.2 v 2.3). People who reported drinking alcohol occasionally or moderately had significantly fewer complaints than teetotalers.CONCLUSIONS: The German Q18 has an acceptable sensitivity and reliability, a reasonable specificity, and a good practicability. It is a useful instrument for screening workers exposed to solvents. A cut off point of 5 for men is recommended, and a cut off point of 6 for women is proposed.Keywords: neurotoxicity; solvents; questionnaire Q18